2021
DOI: 10.1038/s41598-021-85773-7
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced ferroelectric switching speed of Si-doped HfO2 thin film tailored by oxygen deficiency

Abstract: Investigations concerning oxygen deficiency will increase our understanding of those factors that govern the overall material properties. Various studies have examined the relationship between oxygen deficiency and the phase transformation from a nonpolar phase to a polar phase in HfO2 thin films. However, there are few reports on the effects of oxygen deficiencies on the switching dynamics of the ferroelectric phase itself. Herein, we report the oxygen- deficiency induced enhancement of ferroelectric switchin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 52 publications
(31 reference statements)
0
14
2
Order By: Relevance
“…The KAI model is considered appropriate for epitaxial films in classical ferroelectric materials since it describes homogeneous domain nucleus formation and unhindered domain wall motion as the limiting step similar to high-purity bulk materials [ 43 , 48 , 49 ]. However, multiple recent studies have demonstrated that the NLS model is a better fit for HfO 2 thin films [ 34 , 35 , 50 , 51 ]. This model assumes inhomogeneous formation of nuclei in different regions of the film with a characteristic distribution.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The KAI model is considered appropriate for epitaxial films in classical ferroelectric materials since it describes homogeneous domain nucleus formation and unhindered domain wall motion as the limiting step similar to high-purity bulk materials [ 43 , 48 , 49 ]. However, multiple recent studies have demonstrated that the NLS model is a better fit for HfO 2 thin films [ 34 , 35 , 50 , 51 ]. This model assumes inhomogeneous formation of nuclei in different regions of the film with a characteristic distribution.…”
Section: Resultsmentioning
confidence: 99%
“…On the one hand, the stabilizing effect of oxygen deficiency is agreed upon [ 49 , 62 64 ]. On the other hand, the influence on the switching kinetics is controversial, including reports of no direct influence [ 65 ] and switching speed enhancements [ 35 , 64 ]. In the present study, we found faster switching with close to KAI model dynamics for the sample with the higher oxygen content.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the discovery of ferroelectricity more than 100 years ago, many applications have been developed based on its unique property to change the polarization state/orientation using an external electric field. , Based on this bi-stability, ferroelectric (FE) materials became the core of FE random access memory or FE field-effect transistor (FEFET) electronic devices. Even if non-volatility is a key characteristic, the dynamic of polarization switching also plays an important role for binary digital devices and determines important parameters such as the writing speed, writing voltage, stability in time, or fatigue.…”
Section: Introductionmentioning
confidence: 99%
“…The NLS model has also been employed to study the impact of different parameters of HfO 2 on its switching speed. In particular, it has been shown that concentration of oxygen vacancies [ 14 , 15 ], HZO film thickness [ 16 ], and Zr alloy concentration in Hf 1−x Zr x O 2 thin films [ 17 ] affect polarization switching kinetics. On the other hand, the impact of several physical phenomena in HfO 2 on time dependence of polarization switching has been examined in the frame of the NLS model.…”
Section: Introductionmentioning
confidence: 99%